Zero base budgeting: Re-emphasised in India - A case study of research and development organisation - Dhameja, Nand (2002)
Zero Base Budgeting as a concept is still at the experimental stage in various divisions and departments of government. It has born some encouraging results in the resource rich countries, but its efficacy in a developing economy like India needs a careful study. The author while highlighting the features and managerial processes behind Zero Base Budgeting presents case studies pertaining to two of the apex research organisations in India. - Reproduced.
Keywords: Zero base budgeting